Knowledge and practices towards hepatitis B among patients and their attendants in a primary healthcare facility in Bangladesh - Sultana, Rabeya; Imtiaz, Khondker S. (International Journal Of Community Medicine And Public Health, 2020)
Background: Hepatitis B virus (HBV) infection continues to be a major public health issue worldwide. This study assessed the relationship between knowledge and practices towards hepatitis B among patients and their attendants in a primary healthcare facility in Bangladesh. Methods: Respondents’ knowledge and practices were assessed via interviewer-administered questionnaires using a cross-sectional design. The sample size was 204 which was selected conveniently. Chi square testing and binary logistic regression were conducted to examine the relationship between HBV related knowledge and practices. Results: Among 204 respondents 77.9% and 80.4% had poor knowledge and practices respectively about hepatitis B. It was observed that the respondents with adequate knowledge had showed good practice regarding hepatitis B screening (p<0.001), vaccination (p=0.001), screening of blood before transfusion (p=0.018), demanding new syringe before each use (p=0.018), participation in hepatitis B related health education (p<0.001). Furthermore, all the respondents with adequate knowledge group agreed with the statement that they will go for further investigation and treatment if they get infected with HBV (p=0.009). Total knowledge and secondary level of education were significant independent predictors of good practice. OR for knowledge: 1.10 (95% CI: 1.03 to 1.18); OR for secondary level education: 5.66 (95% CI: 1.10 to 29.12). Conclusions: Our results suggest that there is lack of knowledge and practices towards HBV among study population and better knowledge is associated with increased preventive practices. Thus, there is a need for increased HBV education and improved community-based interventions to prevent HBV-related liver disease.